Understanding the Link Between Promotion and Work Performance: A Literature Review in the Context of Regional Water Service Companies - Dewadi, Fathan; Suhara, Ade; Muttaqien, Zaenal (Public Health and Safety International Journal, 2025)
This literature review explores the relationship between promotion and employee work performance within the context of regional water service companies. Promotion is often used as a motivational tool in organizational settings, aiming to reward achievements and encourage higher performance. However, the effectiveness of promotion policies varies depending on organizational culture, fairness, and the clarity of performance metrics. Through thematic analysis of existing research, this study finds that while promotion generally has a positive impact on motivation and commitment, its benefits can diminish when the process lacks transparency or objective criteria. The findings highlight the importance of merit-based promotion systems, coupled with training and support, to ensure that employees succeed in their new roles. This review provides insight for regional service organizations aiming to improve employee performance through well-structured human resource strategies.